Optimal energy portfolio allocation method for regulable hydropower plants considering the impact of new energy generation - Lu, Guanpeng; Yang, Yi; Li, Zhuangzhuang; Tang, Yufeng (Frontiers in Energy Research, 2023)
In deregulated electricity markets， the allocation of energy portfolios significantly impacts hydropower plans' income. Studies have generally considered the impact of spot price and inflow on the income of the energy portfolio of regulable hydropower plants. However, with the growing penetration of new energy sources, the impact of new energy generation on the income of the energy portfolio is becoming more significant. Measuring the income risk of new energy generation on the energy portfolio is one challenge for hydropower plants. This paper proposes a risk measurement method based on the Conditional Value-at-Risk (CVaR) approach, which represents the income loss function of the energy portfolio by the new energy generation. Then, we constructed an energy allocation model of the regulable hydropower plant to maximize the combined income-risk utility. In solving the optimal allocation of the energy portfolio, the effects of inflow and water level on the risk aversion parameters of the hydropower plant are also considered. The results and comparison validate the effectiveness of the energy allocation optimization method.